Perbandingan Administrasi Negara Antara Indonesia dan Singapura Dalam Perspektif Pengelolaan Air Bersih - Emilia, Herlin Putri; Dompak, Timbul (Prosiding, 2024)
Many countries, including Singapore and Indonesia, face critical issues in water management. With a focus on the respective governments, this research discusses and compares the water management approaches between the two countries. Singapore has used innovative technologies such as NEWater and seawater desalination, as well as a centralized and integrated water management system by the Public Utilities Board (PUB), to achieve water self-sufficiency despite its limited water resources. These methods have enabled Singapore to improve its water security and reduce its dependence on imports. However, with more than 270 million inhabitants, Indonesia, the world's largest archipelago, faces complex problems in water management. Some of the key issues include unequal water distribution, inadequate infrastructure, and widespread water pollution. In Indonesia, clean water management involves community-based programs and different levels of government to improve access and quality of clean water. Singapore demonstrates how centralized management and technology can overcome limited natural resources, and Indonesia seeks to address pollution and distribution through infrastructure development and international cooperation. . The results show that water management strategies must be tailored to each country's geographical, economic and social conditions to be successful